2020
DOI: 10.1111/bcp.14564
|View full text |Cite
|
Sign up to set email alerts
|

How often are antidepressants prescribed off‐label among older adults in Germany? A claims data analysis

Abstract: Principal investigator There was no principal investigator, as this study was not an intervention on human subject.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…Off‐label use of antidepressant prescriptions in primary care has been reported as high as 50% in the general population in Canada 11 . Like‐wise, in older adults, a recent German study reported that more than 40% of all antidepressant prescriptions in 2009–2015 were off‐label use 12 . We are not aware of similar data from Denmark.…”
Section: Introductionmentioning
confidence: 80%
See 3 more Smart Citations
“…Off‐label use of antidepressant prescriptions in primary care has been reported as high as 50% in the general population in Canada 11 . Like‐wise, in older adults, a recent German study reported that more than 40% of all antidepressant prescriptions in 2009–2015 were off‐label use 12 . We are not aware of similar data from Denmark.…”
Section: Introductionmentioning
confidence: 80%
“…We do not know if they were actual off‐label uses. Antidepressants' off‐label use has been reported as 44% in German older adults in 2009–2015, 12 40% in Danish children and adolescents in 2006%–2012%, and 29% in a general population of Quebec, Canada in 2003–2015 where TCAs had the highest prevalence of off‐label use. 11 , 12 Differences in definition and assessment criteria (off‐label use in previous studies vs. missing indication in our study), year of study, and country‐specific treatment guidelines perhaps explain the discrepancies in the proportion of off‐label use across the studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors of a previous study based on SHI data of insurants from Baden-Wuerttemberg found a similar prescribing prevalence of antidepressants for this state than we found in our study (Ufer et al , 2007). However, the comparability of results is limited, because most authors of previous studies considering the prevalence of outpatient antidepressant prescribing focused either on specific age groups as children or elderly people, patients with specific diseases, selected drugs or did only consider incident antidepressant use (Hoffmann et al , 2014; Bohlken et al , 2015; Abbas et al , 2016; Booker et al , 2016; Drosselmeyer et al , 2016; Jobski et al , 2017; Schröder et al , 2017a; Boehlen et al , 2019; Forns et al , 2019; Hessmann et al , 2019; Giovannini et al , 2020; Jack et al , 2020; Schäfer et al , 2021). Next to real variations in prescribing practices, implications of manifold methodologies and, particularly in cross-sectional studies, potential seasonal effects must be taken into account when the results of different studies are compared (Gardarsdottir et al , 2010; Abbing-Karahagopian et al , 2014; Mars et al , 2017; Jack et al , 2020).…”
Section: Discussionmentioning
confidence: 99%